Women's Involvement in the Drug Trade: Revisiting the Emancipation Thesis in Global Perspective. Issue 2 (1st February 2023) - Fleetwood, Jennifer; Leban, Lindsay
ABSTRACT: This article undertakes a global review of women's involvement in cultivation, processing, transporting and selling drugs. It is underpinned by twin theoretical concerns. First, we recap and critique the emancipation thesis, especially from a global perspective. Secondly, we examine how diverse global contexts shape women's involvement and the roles they occupy in these economies, challenging the notion that women's involvement in the drug trade is novel, increasing, or attributable to emancipation. Our review shows that women are ubiquitous to the drug trade and women's labor is fundamental to it. Rather than emancipation, we find that contextually-embedded experiences of gender shape women's involvement. We conclude by identifying and thematizing factors better able to explain women's participation in the illegal drug trade and guide future work.